Immediate effects of ultrasound-guided percutaneous neuromodulation versus physical exercise on performance of the flexor hallucis longus muscle in professional dancers: a randomised clinical trial. Issue 2 (April 2019) - de la Cruz-Torres, Blanca; Barrera-García-Martín, Irene; Albornoz-Cabello, Manuel
Background: Ultrasound-guided percutaneous neuromodulation (US-guided PNM) is a minimally invasive intervention. This technique consists of the application of percutaneous electrical stimulation (PES) through an acupuncture needle-like electrode that is placed in close proximity to the nerve or motor point of the target muscle under ultrasound guidance. Objective: To examine the immediate effects of a stretching exercise, an eccentric exercise and US-guided PNM on the performance of the flexor hallucis longus (FHL) muscle in young dancers. Methods: Randomised clinical trial. A total of 45 dancers were divided into three groups: Stretching group, Eccentric group and PNM group. The following performance parameters were assessed: range of motion (ROM) of the first metatarsophalangeal joint, balance test and unilateral heel raise fatigue test. Results: There were no differences between these groups in baseline measurements; at the end of the study, mean balance and endurance values were only significantly higher for the PNM group compared to the Stretching (p = 0.007 and p < 0.001, respectively) and Eccentric groups (p = 0.003 and p < 0.001, respectively). The effect sizes were large for the balance (d = 0.8) and endurance (d = 1.83) tests in the PNM group. Both the Stretching and Eccentric groups exhibited improvements in ROM compared to their baseline values (p = 0.009 and p = 0.004, respectively), whereas there was no significant temporal improvement noted for the PNM group. The effect sizes with respect to ROM values were moderate for stretching (d = 0.6) and eccentric (d = 0.7) exercises. Conclusion: An isolated PES intervention provides a greater immediate increase in balance and muscular strength than an active stretching and eccentric exercise of the FHL muscle in young ballet dancers.